Feature Influence and Brand Image on The Selection of Google Ads as a Moderation Variable in Digital Marketing - Setyawati , Sovy; Lasmiatun, Lasmiatun (Economics and Business International Conference Proceeding, 2024)
The aim of this study For know influence features and Brand Image of Google Ads as a moderating variable in digital marketing (on User Google Ads on the Garudadigital.id Website in Semarang City) In This research used 230 samples with technique purposive sampling with random sampling where each sample or respondents own possibility selected . data used namely primary and secondary data where interviews will be conducted to owner of Garudadigital.id as well user google ads in the city semarang and use analysis correlation as well as linear regression with using SPSS. The research results obtained is (1) feature influential positive and significant to digital marketing with mark significance 0.000 < 0.05. (2) brand image influential positive and significant to decision purchase with mark significance 0.000 < 0.05. (3) Google Ads doesn't capable moderate feature to digital marketing with result 0.681 > 0.05. (4) Google Ads does not moderate brand image towards digital marketing with result 0.349 > 0.05 . Coefficient results determination obtained mark of 0.294, that is that features and brand image as well Google Ads as a moderating variable affects the dependent variable , namely digital marketing by 29.4%.